Kaji Eksperimental Unjuk Kerja Mesin Diesel Memanfaatkan Campuran Biodiesel Dari Biji Alpukat (Persea Americana) - Muhammad Ilham Maulana; Khairil Khairil; Rizal Aiyubi (Jurnal Teknik Mesin Unsyiah, 2019)
The availability of fossil fuels is increasingly decreasing, so some researchers have to look for alternative fuels, namely biodiesel. The raw material used as biodiesel was avocado seeds planted in Indonesia. Avocado seed oil content ranges from 15-25%. The purpose of this study was to determine the characteristics of biodiesel and diesel engine performance testing. This biodiesel is obtained through the esterification and transesterification process. This research uses a mixture of avocado seed oil biodiesel fuel with Pertamina dex fuel namely (B-5) 5%:95%, (B-15) 15%:85%, and (B-25) 25%:75% and (B-0) as a comparison. The test was carried out at the Engine and Propulsion System Laboratory at Mechanical Engineering Department, Universitas Syiah Kuala. The diesel engine was used is RUGGERINI HT-51 with a maximum power of 3 kW/3600 rpm. Biodiesel from avocado seed was tested physicochemical characteristics; the result is in accordance with National Standard (SNI) for biodiesel fuel. Performance results show the B-15 fuel produces the best engine performance at 3500 rpm. At this cycle a maximum power of 1.90 kW is obtained, the lowest specific fuel consumption rate of 2000 rotation (rpm) is 0.34 kg / kW hour on B-15 fuel, and the highest thermal efficiency on B-15 fuel with 2000 rotation (rpm) is 14.05%.